The naughtiest unicorn on the beach - Bird , Pip; O'Connell, David (London Egmont, 2020)
Blow up your inflatable, apply the factor 50 and polish those sunnies... Mira and Dave the naughtiest unicorn are going to the BEACH! Mira can't wait to build a GIANT sandcastle (although Dave is more interested in eating a GIANT GLITTERY ICE-CREAM). But when Mira and her Unicorn School friends go exploring and spot a little narwhal in BIG trouble, the fun day out turns into a super-adventurous rescue mission... it's Dave and Mira to the RESCUE!
English stories
Keywords: Beaches; Children's stories